Análisis comparativo del periodismo 2.0 en los medios de comunicación TC Televisión y Ecuavisa - Tomalá Manjarréz, Haidee Yolanda (2020)
This research work is carried out with the purpose of analyzing and comparing journalism 2.0 of the media TC Televisión and Ecuavisa, through social networks, since these are a large part of digital journalism; Taking the social network Facebook as an example. According to the research carried out, it can be observed that thanks to the digitalization that has advanced over time, there is greater immediacy in the information transmitted daily by the media that have had their convergence to the Internet, being a great tool Importance for society. Some authors state that the digital communicator must be creative when publishing content for the audience, in order to capture the attention of the person who consumes the information; In addition to creativity, a journalist dedicated to digital media. In order to perform this comparative analysis, a diagnosis was made of the TC Televisión and Ecuavisa media about their treatment of information and news content on the social network Facebook; The students of the eighth semester of the social communication career at the Technical University of Babahoyo were also taken as a sample for their respective survey; In turn, ask each of the respondents if they are prepared to practice digital journalism. Of the people surveyed, through the diagnostic technique, they mostly assured that there was little knowledge about journalism 2.0 and some indicated that they were not prepared to practice in this field.